Ta'zîzu Dâfi'iyyati Thullâbi Riyâdh al-Athfâl li Tathwîri Mahârât al-Lughah al-'Arabiyyah al-Syafawiyyah min Khilâli Barâmiji al-Ta'lîm al-Mukatstsaf - Hadi, Nurul; Alvina, Nuri; Khaled Radhouani (IAIN Madura, 2024)
This research study was motivated by several key factors. Firstly, the Arabic language holds great religious and cultural significance in Indonesia, as it is a core component of Islamic identity and practice, particularly in the context of Quranic education for children. However, many students at Quranic preschools struggle with developing proficiency in spoken Arabic. Additionally, educational literature emphasizes the critical role of student motivation in facilitating effective language learning outcomes. Therefore, it was important to investigate the factors influencing students' motivation to learn Arabic in this specific educational setting. Moreover, most prior research in this field has been conducted in non-Indonesian contexts, necessitating localized studies to explore the nuances of the Indonesian educational dynamics. Ultimately, this research aimed to help address the gaps in the existing body of knowledge around Arabic language instruction in Indonesian Quranic preschools. The researcher employed a quantitative approach and simple linear regression to analyze data collected from interviews, observations and questionnaires. Statistical tests of validity, reliability, normality, linearity and correlation were performed on the questionnaire data using SPSS. The iresults ishowed ithat iintensive Arabic classes had a significant effect on students' motivation to learn speaking skills, as idemonstrated iby ia ip-value iof iless ithan i0.05. Regression analysis further reported that these classes influenced motivation by 33.1%, as indicated by the R-squared value. Therefore, the intensive language exposure appeared to positively impact the kindergarteners' drive to develop their Arabic communication abilities.